TRIBAL SURVIVAL IN THE URBANIZED WORLD: A PARADOX OF CHANGE - Jangir, Priyanka; Kumar, Anupam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of this research paper is to investigate how urbanisation frequently brings challenges for tribal communities impacting their customs, ways of life, and access to land and its resources. This paper examines the difficulties tribal communities encounter and negotiate their identities in urban settings. Now, the tribal communities, in the midst of urbanisation, confront a paradox where economic opportunities and social problems co-exist. Although urbanisation brings better employment opportunities, educational opportunities, and infrastructure, these advantages frequently come at the expense of cultural assimilation, land loss, and tribal populations being uprooted. Urbanisation’s dual nature brings both benefits and risks for tribal communities. This research paper contributes to the existing knowledge available on tribal communities and urbanisation by providing a nuanced understanding of the dynamic process of urbanisation and its impact on tribals. To navigate this intricate urbanisation paradox, it becomes crucial to strike a balance that upholds tribal identity, guarantees equitable development, and protects cultural legacy.